Prevalence, treatment seeking behaviopur and correlates of migraine and tensiontype headache among 20- 59 year old adults in the Gampaha District of Sri Lanka and comparison of health related quality of life of adults with migraine and those without headache disorders. - Perera, G.S.N (My University, 2007)
Main objective of the study was to determine the period prevalence of migraine and TTH among 20-59 year old adults in the Gampaha district. Other objectives were development and validation of a screening instrument named HHQ-Sri Lank to determine migraine and TTH in the community, determination of treatment seeking behavior and correlates of migraine and TTH and comparison of health related quality of life among adults with migraine and those free of a headache disorder. The study consisted of three phases. First was to develop and validate HHQ-Sri Lanka@ to identify sufferers of migraine and TTH, second to determine the prevalence, treatment seeking behavior and correlates of migraine and TTH and the third to compare the quality of life among mariners and those free of headache disorders. The clinical diagnosis made by the Consultant Neurologist based on the International Classification of Headache Disorders (ICHD 11), which was considered as the gold standard. Sensitivity of HHQ-Sri Lankar in identifying migraine was 89.8 percent (95 percent CI: 76.8 - 96.2) and the specificity was 95.7 percent (95 percent CI :91.2 - 98.2). Positive and negative predictive values were 88.0 percent (95 percent CI: 76.7 - 95.0) and 96.4 percent (95 percent CI: 92.1. - 98.7) respectively.